2021
DOI: 10.1097/ijg.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beta-zone Peripapillary Atrophy and Focal Lamina Cribrosa Defects on Peripapillary Vessel Parameters in Young Myopic Eyes

Abstract: Precis: The development of beta-zone peripapillary atrophy (β-PPA) and focal lamina cribrosa defect (FLD) was significantly associated with decreased peripapillary optical coherence tomography angiography (OCTA) vessel parameters in young myopic eyes. Purpose: The purpose of this study was to investigate whether β-PPA and FLD affect peripapillary vessel density (VD) or perfusion density (PD) from OCTA in young myopic eyes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The findings of the present study possibly explain the phenomenon of topographic distribution of localized LC defect and its association with glaucoma. Previous studies have shown that large LC pores and LC defects are located mostly on the temporal rather than the nasal side 27 , 28 . We can postulate that axial-elongation-associated stretching of the temporal LC generates tensile force that results in localized LC defect on the temporal side.…”
Section: Discussionmentioning
confidence: 98%
“…The findings of the present study possibly explain the phenomenon of topographic distribution of localized LC defect and its association with glaucoma. Previous studies have shown that large LC pores and LC defects are located mostly on the temporal rather than the nasal side 27 , 28 . We can postulate that axial-elongation-associated stretching of the temporal LC generates tensile force that results in localized LC defect on the temporal side.…”
Section: Discussionmentioning
confidence: 98%
“…40,43 Also, a considerable number of myopic eyes (average AXL 25.0 mm) were included in this study, thus limiting the applicability of those 2 parameters. Given that both MvD and focal LC defects can be observed in eyes the myopia, 44,45 further studies on the development of vascular and structural changes of the deep ONH tissue in myopic glaucomatous eyes are warranted. Fourth, eyes with diabetes, hypertension, and various glaucoma medications were included in this study, and this may be the potentially confounding factor related to the vascular parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, this conclusion might not be applicable to highly myopic eyes, as researchers excluded eyes with myopic tilted disks and gamma zones. Choe et al initially demonstrated a significant reduction in PVD or perfusion density (PD) using OCTA with the development of focal LC defects in young myopic patients, suggesting an increasing risk of glaucoma in the future ( 43 ).…”
Section: Papillary/peripapillary Tissue Defectmentioning
confidence: 99%